Active frequency selective surface with switchable response for satellite communications in X and Ka bands. Issue 9 (27th May 2022) - Abdollahvand, Mousa; Martinez‐de‐Rioja, Eduardo; Forooraghi, Keyvan; Atlasbaf, Zahra; Encinar, José Antonio; Ghosh, Saptarshi; Ebrahimi, Amir
Abstract: This article proposes an active frequency selective surface (FSS) with application to satellite multi‐band antennas in X and Ka bands. The FSS offers two reflective bands at 20 and 30 GHz (downlink and uplink frequencies of broadband communication satellites in Ka‐band) under one biasing state, whereas the frequency characteristics are switched in X‐band (between 9 and 12 GHz, frequencies used for broadcast satellite services and space exploration) under the second biasing state. The unit cell of the FSS consists of three metallization layers, including four PIN diodes on the bottom layer that provide reconfigurability in X‐band. The FSS performance has been analyzed using an equivalent circuit model diagram, which provides a better understanding of the operation principle. The proposed FSS exhibits a robust transmission response for incidence angles up to 40°. Several samples of the FSS formed by a 2 × 4 cell array have been fabricated and measured in a waveguide simulator to confirm the results of the electromagnetic simulations at the lower operating frequencies.